Women’s Associations and children’s rights in Italy (1861-1930) - Gabriella Seveso; Daniela Finco (Zero-a-seis, 2017)
The aim of this article is to present the diffusion of educational institutions for Italian young children and the way in which it is significantly linked to women’s associations and the initiatives of illuminated thinkers. The article reconstructs the history of the right to education for early childhood in Italy in the period between the Unification of Italy (1861) and the first decades of the twentieth century. It reveals how these initiatives emphasized the need to provide educational institutions for young girls and young boys, not only for the purposes of care or hygiene; but often with important educational principles such as attention to spaces, relationships with families, and others. The article also points out how the women’s association also fought hard for adequate professional training of teachers and teachers.